2020
DOI: 10.7759/cureus.8719
|View full text |Cite
|
Sign up to set email alerts
|

Association of Opioid Use With Cardiometabolic Disease Risk Factors: Evidence From the 2009-2018 National Health and Nutrition Examination Survey

Abstract: Objective To investigate the association between opioid drug use and cardiometabolic risk factors in an adult sample data acquired from the National Health and Nutrition Examination Survey (NHANES). Methods A retrospective cross-sectional analysis was performed using the data from the NHANES for the period 2009-2018 provided by the Centers for Disease Control and Prevention (CDC), amounting to a total of N = 10,032 eligible participants. The data were analyzed to study the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Approximately a third of the sampled population had increased waist circumference with 12% having low HDL. These ndings correlate with those of Shah et al [22] who showed that history of ever use of any drug was associated with increased odds of elevated waist circumference and decreased odds of having low HDL.…”
Section: Discussionsupporting
confidence: 89%
“…Approximately a third of the sampled population had increased waist circumference with 12% having low HDL. These ndings correlate with those of Shah et al [22] who showed that history of ever use of any drug was associated with increased odds of elevated waist circumference and decreased odds of having low HDL.…”
Section: Discussionsupporting
confidence: 89%
“…Approximately a third of the sampled population had increased waist circumference with 12% having low HDL. These findings correlate with those of [22] who showed that history of ever use of any drug was associated with increased odds of elevated waist circumference and decreased odds of having low HDL.…”
Section: Discussionsupporting
confidence: 86%
“…Other studies showed a less clear linkage between OUD and metabolic syndrome. A retrospective cross-sectional study of 10,032 subjects showed that drug use was linked to a higher waist circumference but did not find a significant association between drug use and clusters of three or more cardiometabolic disease risk factors (impaired glucose tolerance, insulin resistance, hypertension, dyslipidemia, and central adiposity) (9). Complicating this linkage is that adults with OUD have multiple life stressors and psychiatric comorbidities that may contribute to the development of metabolic syndrome (34,35).…”
Section: Metabolic Syndrome In Adults With Opioid Use Disordermentioning
confidence: 99%
“…Rodents exposed to opioids develop drug-induced obesity and DM type 2 (6), while administration of opioid antagonists reduces opioid craving and appetite for palatable food leading to weight loss (7,8). The exact mechanisms by which drug addiction and metabolic syndrome are linked together are of growing interest, with some reporting no direct association (9), while others reporting disrupted reward circuitry, i.e., dopamine receptors, as a common denominator between opioid addiction, food dependence and obesity (10)(11)(12). To close this knowledge gap, our laboratory examines the expression of hypothalamic and reward genes that regulate feeding behavior in opioidexposed neonates, with evidence of abnormal reward signaling and behavioral changes that may predispose these neonates to long-term growth and metabolic issues (13).…”
Section: Introductionmentioning
confidence: 99%